Raconter la Partition de l’Inde : une impossible histoire des femmes ? - Anne Castaing (Genre & Histoire)
After many years subjected to a vision of history dedicated to the glorification of the nation, the Partition of India (1947) has attracted renewed interest in the last thirty years or so, aiming to shed as much light as possible on this popular tragedy and its subaltern histories. The history of women has been one part of this movement, even if belatedly so, and the historiography of “Subaltern Studies” has shed light on role of women, as well as the strategies of invisibilization and instrumentalization to which they have been subjected in nationalist histories. This history “read against the grain” has been accompanied by a revaluation of “historical sources” themselves, as evidenced by numerous publications that drew from alternative sources: testimonies, life stories, but also literature or cinema, thus voicing the silent histories of Partition. Beyond the historical reading of fiction, however, a literary reading reveals some ambiguities and contradictions in the strategies that aim at giving voice to subaltern characters, and notably women. Can literature really allow us to reconstruct a women’s history of this period? What aid might it provide for feminist initiatives, and what historical perspectives emerge from it? In the light of literary texts written in the aftermath of Partition, this article aims to question the paradoxical role of literary texts in creating the master narratives of Partition, and more specifically in reconstituting a women’s history.